1991
DOI: 10.1002/jor.1100090410
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of lidocaine following topical application in microvascular procedures on rabbits

Abstract: Fifty rabbits were used to investigate the absorption of lidocaine following its topical application to blood vessels. The lidocaine level in the blood was determined by gas chromatography and the enzyme immunoassay. Animals were divided into five groups according to anatomic site (femoral vs iliac) and according to whether vessels were intact or anastomosed. In the last group (E), a water-tight sleeve was placed on the anastomosed femoral artery so that the lidocaine contacted only a small segment of the arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…2 It is characterized by wide availability, low cost, and rapid spasmolytic and antispasmodic effect. 5,11 In addition, despite quick tissue penetration, 5 large topical doses lead to negligible serum levels. 12 In this study, dilated arteries in the delayed group did not dilate further when exposed to 2% lidocaine, suggesting that maximum vasodilation had already been achieved 24 hours earlier by hydrostatic dilation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2 It is characterized by wide availability, low cost, and rapid spasmolytic and antispasmodic effect. 5,11 In addition, despite quick tissue penetration, 5 large topical doses lead to negligible serum levels. 12 In this study, dilated arteries in the delayed group did not dilate further when exposed to 2% lidocaine, suggesting that maximum vasodilation had already been achieved 24 hours earlier by hydrostatic dilation.…”
Section: Discussionmentioning
confidence: 98%
“…4 Pharmacological agents, such as lidocaine, are less traumatic but do not always promote vasodilatation to the desired extent. 5 Even under the best of circumstances, simple dissection and exposure of the rat femoral vessels can lead to denudation of the intima and ischemic lesions of the tunica media. This damage may be caused by removal of the vasa vasorum during the dissection.…”
mentioning
confidence: 99%
“…The effectiveness of lidocaine is known to be strongly related to its concentration. [7][8][9][10] It has been reported that 20% lidocaine is the optimal concentration. 4,7 On the other hand, the occurrence of clinical toxicity has been reported when high-concentration lidocaine is directly applied on a vessel.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 On the other hand, the occurrence of clinical toxicity has been reported when high-concentration lidocaine is directly applied on a vessel. 10 Beekman and Persisting effect of lidocaine application immediately after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic absorption of the topically applied lidocaine is rapid, with a peak occurring at 5 to 15 minutes 9 . The perivascular tissue is regarded as the most important site of absorption 9 . This may be a result of the mixing of lidocaine with blood at the anastomosis and slower blood flow at this site 9 .…”
Section: Discussionmentioning
confidence: 99%